Enhancing Digital Literacy through Differentiated Learning in Islamic Religious Education at SMAN 1 Rogojampi - Baraz Yoechva Alfaiz; Siti Aimah (Ta'dib, 2025)
Digital developments can change the way information and knowledge are disseminated, including in learning Islamic religious education. The application of differentiated learning can increase the effectiveness of the educational process, especially in improving digital literacy. Learning differentiation focuses on adjusting the learning process. Therefore, in general, the purpose of this study is to find out how PAI teachers use effective differentiation strategies to improve students' digital literacy, challenges in implementing differentiated learning in improving digital literacy and religious literacy in the school environment, and strategies in dealing with digital literacy obstacles among students. This study uses a qualitative descriptive approach to gain in-depth insight into the strategies applied by PAI teachers in improving digital literacy at SMAN 1 Rogojampi. The results of this study are (1) content differentiation; students' understanding of Islamic Civilization material is increased, especially in the presentation of language that is more contextual and easy to understand, (2) process differentiation; Collaboration in groups can help ISWA exchange Islamic information using digital media, (3) product differentiation; Provide practical exercises directly, such as creating simple digital da'wah content or digital-based projects. In general, this research produces information about improving the ability to access, evaluate, manage information, and strengthen digital literacy based on Islamic values, especially material (Islamic Civilization. Teachers' strategies in overcoming obstacles are (1) making individual assessments as a basis for determining basic learning needs in the context of differentiating content, processes, and products. (2) Provide alternative teaching materials in various formats (online and offline), and (3) provide hands-on practical exercises using digital-based projects.